Ordinances of the Town of Columbia 61-62 (1823) - (:unkn) unknown (My University, 1823)
No. 41: That hereafter it shall not be lawful for any person to fire or discharge any gun, pistol or other small arms within the limits bounded by Henderson, Blossom, Lincoln and Upper streets
Keywords: DISCHARGE